2010
DOI: 10.1590/s0370-44672010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Atrito interno em aços inoxidáveis austeníticos contendo cobre

Abstract: ResumoNesse trabalho, estudaram-se a infl uência dos tipos e as quantidades de martensitas induzidas por deformação nas curvas de atrito interno de um aço inoxidável do tipo ABNT 304 contendo cobre. Corpos-de-prova foram deformados por tração de 3 a 12% de deformação verdadeira em temperaturas no intervalo de 50 a 20ºC, visando à obtenção de diferentes quantidades das fases martensíticas  (HC) e ' (CCC). Medidas magnéticas e ensaios dilatométricos foram realizados para avaliar as quantidades induzidas. Verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Previous dilatometric studies revealed e fi c reverse transformation between RT and 473 K (200°C) and a¢ fi c reverse transformation in the range of 773 K to 1073 K (500°C to 800°C). [3,20] Both (e fi c, a¢ fi c) transformations are shifted to higher temperatures with the increase of heating rate (at the heating rate higher than 0.1 K/s). [21] Tomimura et al described two types of possible reverse transformation (a¢ fi c) mechanisms: 1st diffusive by nucleation and growth of new austenite grains and 2nd diffusionless shear reversion.…”
Section: Introductionmentioning
confidence: 99%
“…Previous dilatometric studies revealed e fi c reverse transformation between RT and 473 K (200°C) and a¢ fi c reverse transformation in the range of 773 K to 1073 K (500°C to 800°C). [3,20] Both (e fi c, a¢ fi c) transformations are shifted to higher temperatures with the increase of heating rate (at the heating rate higher than 0.1 K/s). [21] Tomimura et al described two types of possible reverse transformation (a¢ fi c) mechanisms: 1st diffusive by nucleation and growth of new austenite grains and 2nd diffusionless shear reversion.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados semelhantes observados para aços inoxidáveis do tipo 304. (8,9) No aço 304N não foi possível distinguir um terceiro pico em 140°C. Este pico, no entanto, torna-se visível por meio da decomposição da curva de atrito interno em seus componentes básicos (Figura 8b).…”
Section: ε α'unclassified